Mental health, gender and remote teaching during COVID-19 lockdown in Mexico - Saldívar-Garduño, Alicia (2020)
Due to the COVID-19 pandemic caused by the emergence of a novel virus called SARS-CoV-2 in the world, and its subsequent arrival in Mexico, the Federal Government and the National Health Council declared on March 23 the start of the National Season of Healthy Distance to prevent the mass spread of the virus, which included the suspension of in-person classes at all levels. In this situation, school communities faced an uncertain and unknown scenario, and suddenly had to continue the educational work in a remote way. This scenario has led to changes in habits and routines, and has affected the mental health of both academic staff and students, who experience stress, tiredness and frustration due to the excessive workload, lack of technological skills, and gaps in adapting to “the new normal.” Gender inequality, which significantly affects women, has also been clearly seen because of the multiple roles they must play during quarantine as mothers, students, family caregivers and providers of care for sick family members.